Understanding the Process of Illness in Childhood: Exploring Meanings for Health Promotion - Praxedes, Amanda Emília Nunes Quezado; Daniele, Thiago Medeiros da Costa; Frota, Mirna Albuquerque; Pinto, Nilson Vieira; Cardoso, Maraysa Costa Vieira; Rebouças, Diane Nocrato Esmeraldo; Pinheiro, Monica Helena Neves Pereira; Costa, Matheus Marques Mesquita da (Seven Editora, 2023)
The diagnosis of childhood cancer changes the lives of children and their families. Hospitalization in pediatric oncology presents challenges for the health team, which seeks to promote an environment in which children feel safe and their biopsychosocial needs are met. Thus, the objective was to understand, in the specialized literature, the meanings of the disease process for the child and, based on this, to seek ways to improve this process through health promotion. This is an integrative literature review, using the Lilacs and Medline databases, with the Health Sciences Descriptors: "child", "neoplasia" and "health promotion". As inclusion criteria, the study focused on articles involving the research theme, available in full in full, published between 2006 and 2016, in Portuguese, English and Spanish. Those in the form of monographs, theses, dissertations and annals of papers presented at events were excluded. The search for the analysis material resulted in a total of 214 articles, and ten articles were selected according to the inclusion criteria. Of the ten articles, eight focused on health promotion actions and of these eight, five addressed humanization in health as the main strategy. The diagnosis provokes several emotional reactions in the parents, in the child and in all those inserted in their context. Another action for health promotion is to work with play, which brings benefits to the child and to the treatment, serving as a strategy to cope with hospitalization. With regard to the family, the literature has indicated priorities for research in the area on experiences with the disease. After the review, it can be seen that the literature is still scarce regarding the child, because the child's perspective in relation to the disease and diagnosis is little addressed. The synthesis of the knowledge produced by the present study provides a framework of empirical evidence that allows us to affirm that the effort to understand the experiences and challenges experienced by pediatric patients and their family caregivers can help in the organization of comprehensive care in this delicate stage of treatment. DOI:https://doi.org/10.56238/innovhealthknow-035